2005
DOI: 10.1523/jneurosci.2532-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

HighwireFunction at theDrosophilaNeuromuscular Junction: Spatial, Structural, and Temporal Requirements

Abstract: Highwire is a huge, evolutionarily conserved protein that is required to restrain synaptic growth and promote synaptic transmission at the Drosophila neuromuscular junction. Current models of highwire function suggest that it may act as a ubiquitin ligase to regulate synaptic development. However, it is not known in which cells highwire functions, whether its putative ligase domain is required for function, or whether highwire regulates the synapse during development or alternatively sets cell fate in the embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
171
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(181 citation statements)
references
References 32 publications
10
171
0
Order By: Relevance
“…These data argue that specific loss of the Hiw Ring domain-which would lead to a protein predicted to bind its substrate but not transfer ubiquitin-can dominantly suppress axon degeneration. Consistent with this notion, Gal4/UAS-mediated overexpression of Highwire containing a nonfunctional RING domain (HiwΔRING) in wild-type animal phenocopies loss of hiw function both in NMJ morphological defects and axon degeneration (13,29). Our observation that both hiw 403d and hiw 275d fully suppress axon degeneration for 1 wk after axotomy argues for a key role for the Hiw RING domain in axon death signaling.…”
Section: Rapid Identification Of Dominant and Recessive Highwire Allelessupporting
confidence: 75%
See 2 more Smart Citations
“…These data argue that specific loss of the Hiw Ring domain-which would lead to a protein predicted to bind its substrate but not transfer ubiquitin-can dominantly suppress axon degeneration. Consistent with this notion, Gal4/UAS-mediated overexpression of Highwire containing a nonfunctional RING domain (HiwΔRING) in wild-type animal phenocopies loss of hiw function both in NMJ morphological defects and axon degeneration (13,29). Our observation that both hiw 403d and hiw 275d fully suppress axon degeneration for 1 wk after axotomy argues for a key role for the Hiw RING domain in axon death signaling.…”
Section: Rapid Identification Of Dominant and Recessive Highwire Allelessupporting
confidence: 75%
“…Thus, the Hiw RING domain is a key functional domain required to drive axonal degeneration. It remains to be determined how these dominant hiw alleles block axon degeneration (13,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bouton analysis. Quantification of bouton number and size was performed as described previously (Wu et al, 2005) using confocal images analyzed with MetaMorph software (Universal Imaging Corporation). Wandering third-instar larvae were costained for antibody to HRP and DVGLUT.…”
Section: Methodsmentioning
confidence: 99%
“…Work in Drosophila and Caenorhabditis elegans showed that in the absence of the E3 ubiquitin ligase Highwire (Hiw; RPM-1 in C. elegans), Wnd levels increase, overactivating the Jnk pathway (Nakata et al 2005;Collins et al 2006). Loss of function of hiw gives rise to a distinct synaptic morphology characterized by a greatly expanded arbor and abnormally small boutons ( Figure 5B) (Wan et al 2000;Wu et al 2005). Despite the increase in bouton number, these animals exhibit synaptic dysfunction with decreased quantal size and quantal content.…”
Section: Mechanisms Regulating Growth and Plasticitymentioning
confidence: 99%